Acousto-optic modulator based dispersion scan for phase characterization and shaping of femtosecond mid-infrared pulses - Nicolai, Florian; Müller, Niklas; Manzoni, Cristian; Cerullo, Giulio; Buckup, Tiago (Optics express, 2021)
Compression, shaping and characterization of broadband mid-infrared (MIR) pulses based on an acousto-optic modulator (AOM) pulse shaper is presented. Characterization of the spectral phase is achieved by an AOM-shaper based implementation of a dispersion scan (d-scan). The abilities of the setup are demonstrated by imprinting several test phases with increasing complexity on broadband MIR pulses centered at 3.2 µm and retrieval of the imprinted phases with the presented d-scan method. Phase characterization with d-scan in combination with an evolutionary algorithm allows us to compress the MIR pulses below 50 fs FWHM autocorrelation after the shaper.
Gesehen am 17.08.2021